Processed bed elevation picks from airborne radar depth sounding from the FISS 2015 survey covering the Foundation Ice Stream and the Filchner Ice Shelf system (2015/2016) ... - Nicholls, Keith; Robinson, Carl; Corr, Hugh; Jordan, Tom (NERC EDS UK Polar Data Centre, 2021)
This dataset contains bed and surface elevation picks derived from airborne radar collected in 2015/16 over Foundation Ice Stream and Filchner Ice Shelf as part of the 5-year Filchner Ice Shelf System (FISS) project funded by NERC (grant reference number: NE/L013770/1) and awarded to the British Antarctic Survey with contribution from the National Oceanography Centre, the Met Office Hadley Centre, University College London, the University of Exeter, Oxford University, and the Alfred Wenger Institute. The aim of this project was to investigate how the Filchner Ice Shelf might respond to a warmer world, and what the impact of sea-level rise could be by the middle of this century. This collaborative initiative collected ~7,000 line-km of new aerogeophysical data using the 150MHz PASIN radar echo sounding system (Corr et al., 2007) deployed on a British Antarctic Survey (BAS) Twin Otter. ... : Radar data were collected using the new bistatic PASIN-2 radar echo sounding system mounted on the BAS Twin Otter aircraft "VP-FBL" and operating with a centre frequency of 150 MHz and using a 4-microseconds, 13 MHz bandwidth linear chirp. Data provided here includes picks and derived elevations of the ice sheet surface and bed. The radar data was processed using a coherent averaging filter (commonly referred to as unfocused Synthetic Aperture Radar (SAR) processing) with Doppler beam sharpening to enhance the signal to clutter ratio of the bed echo and improve visualisation. The received chirp of 4 microseconds, 13 MHz bandwidth data was compressed, filtered, and decimated from the original trace acquisition rate of 156.25 Hz to 5Hz, equivalent to ~11m in along-track spacing. The bed reflector was first automatically depicted on the chirp data using a semi-automatic picker in the PROMAX software package. All the picks were afterwards checked and corrected by hand if necessary. The picked travel time was ...